Erythrocyte alkaline phosphatase in patients with myotonic muscle disorders - Goldemberg, Adriana Lía; Madrid, Enrique Alberto; Garcia, Alicia Mabel; Roubicek, Martín; Trucco, Raúl Esteban (Investigación Clínica, 2013)
The allosteric behaviour of the p-nitrophenyI-phosphatase (E.C.3.1.3.l.) from membrane erythrocytes was investigated in the following multisystemic diseases: myotonic dystrophy, limb-girdle muscular dystrophy. Charcot-Marie-Tooth and juvenile spinal muscular atrophy; in myotonia congenital, which is not a multisystemic disease, and in healthy controls. The Hill coefficient in F-inhibition in controls was different from that in multisystemic diseases patients but not from that in myotonia congenita patients. Changes in the cooperative type kinetics would suggest that the interaction membrane-enzyme in controls and in patients with neuromuscular disorders is onIy different for multisystemic diseases.